Social Identity and Sectarianism in the Qumran Movement. - Jokiranta, Jutta (Studies on the texts of the desert of Judah., 2012)
'Identity' and 'sectarianism', two crucial and frequently used concepts in the study of the Qumran movement, are problematized, praised, and redefined in this book. Sociology of sectarianism and social identity approach inform the investigation of the serakhim (rule documents) and pesharim (biblical commentaries).